KOMUNIKASI ORGANISASI DALAM PENERAPAN LIMA NILAI BUDAYA KERJA PADA PELAYANAN HAJI DI KANTOR KEMENTERIAN AGAMA KOTA PEKANBARU - Aulia Permata Sari; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Work culture is a philosophy based on the view of life as values that become the nature, habits and driving forces, entrenched in the life of a group of society or organization. In 2015 the work culture has been set by the Ministry of Religious Affairs of the Republic of Indonesia to become one of the guidelines of employees in carrying out their duties and responsibilities in work. Before the five work culture in the Office of the Ministry of Religious Pekanbaru city employees are still less discipline in work after the existence of these five cultural will facilitate employees in running duties and responsibilities as an employee. The purpose of this research is to know the application of the five values of work culture at the Hajj service at the Office of Religious Ministry of Pekanbaru city.Descriptive approach of qualitative method was used in this study. Research subjects are Section Head Hajj and Umrah operations, employees in Section Hajj and Umrah, Hajj Pilgrimage and Candidate Hajj pilgrims and pilgrims taking subject based on purposive methods. The object of research is the application of work culture. In Techniques collecting the data the researcher conducted interviews, observation and documentation.The results of this study indicate that the application of the five values of work culture seen in terms of communication down and up. Integrity, communications by conducting coaching to employees while communication to the problem in the service of Hajj. Professionalism, communication downstairs and providing good examples while communication upwards at the meeting. Innovation, communication below provides guidance and supervision while communication upwards requesting a proposal to superiors. Responsibility of communication down by giving the task of communication up to him giving a monthly job report. Exemplary, communications given the discipline in the form of discipline while communicating the issues of opinion in the service of Hajj. Communication barriers can be divided into two parts: technical barriers and human barriers. Technical barriers such as lack of existing facilities and infrastructure need support from superiors about the problems of facilities and pre-facilities. Human barriers are a factor in the prospective pilgrims and different pilgrims and employees should be responsible for serving pilgrims and pilgrims.